A CASE REPORT ON A RARE ANOMALY: BARTSOCAS PAPAS SYNDROME - RUGMINI KAMMALAMMAL; SURESH KIRUPANANDHAN (International Journal of Pharma and Bio Sciences, 2013)
Bartscoas Papas syndrome (BPS) presents a rare and lethal anomaly characterised by severe popliteal pterigyum, mid facial defects, syndactyly and genital abnormalities. The purpose of presenting this case is its rarity and its presentation with normal amount of liquor and normal foetal movements which is not hitherto reported. Previous reported cases which were diagnosed during the antenatal period had family history of similar disorder. But this case had no history of similar anomaly in the family.